Fasting Ramadan in patients with T1DM – Saudi Arabia versus other countries during the COVID-19 pandemic. Issue 1 (January 2023) - Alamoudi, Reem M.; Aljohani, Naji J.; Alfadhli, Eman M.; Alzaman, Naweed; Alfadhly, Abdulaziz F.; Kallash, Majd-Aldeen; Alshenqete, Abdulwadod M.; Batais, Mohammed A.; Alharbi, Mansour; Ekhzaimy, Aishah A.; Sheshah, Eman; Ahmedani, Muhammad Yakoob; et al.
Abstract: Background and aims: To compare Saudi Arabia with other countries regarding patient attitudes towards fasting Ramadan and complications related to fasting during the COVID-19 pandemic. Methods: Data collected from Saudi Arabia and 12 other mostly Muslim majority countries, via physician administered questionnaire within post Ramadan 2020. Results: 1485 Type1 diabetes (T1DM) patients analyzed; 705 (47.5%) from Saudi Arabia vs. 780 (52.5%) from other countries. 1056 (71.1%) fasted Ramadan; 636 (90.2%) of Saudi patients vs. 420 (53.8%) of other countries. Experiencing Ramadan during the COVID-19 pandemic did not affect the Saudi T1DM patients' decision to fast while it significantly influenced their decision in other countries (1.4 vs 9.9%, P < 0.001). More Saudi patients needed to break the fast due to a diabetes related complication compared to other countries (67.4% vs. 46.8%, p=<0.001). The mean number of days fasted in Saudi and other countries was 24 ± 7 and 23 ± 8 days respectively. Hypoglycemic events were more common among Saudi patients during Ramadan compared to other countries 72% and 43.6% (p < 0.001) respectively. There was a significant difference in timing; the largest peak for Saudi Arabia patients was after dawn (35% vs 7%, p < 0.001), while it was pre-sunset for the other countries (23 vs 54%, p = 0.595). Day time-hyperglycemia was also more common among Saudi patients (48.6% vs. 39%, p < 0.001), however it was a less likely cause to break the fast (25.6% vs 38.3%, p < 0.001). Conclusion: Observing the fast of Ramadan is extremely common among Saudi T1DM patients compared to other Muslim countries and was not affected by the COVID-19 pandemic. However, it was associated with higher frequency of hypoglycemic and hyperglycemic episodes. Highlights: Study Highlights. Fasting Ramadan is routine practice for Saudi type1 diabetes patients. Saudi patients reported higher rates of hypoglycemic and hyperglycemic episodes. Timing of hypoglycemia during fasting was significantly different in Saudi patients. More Saudi patients received virtual type education during the COVID pandemic.